Bridal Shower in Yogyakarta: The Shifting of Meaning and the Shaping of Social Class - Vidiadari, Irene Santika; Rismayanti, Rebekka (Universitas Muhammadiyah Ponorogo, 2022)
Bridal shower, a modern ritual of Indonesia modern society, has as well been practiced by people living in Yogyakarta. The adopted â€œAmerican bridal showerâ€ had been the representation of high-class society for it emphasized on luxurious symbols. Now, the trend has spread to the middle-class and has become a part of pre-wedding events. Yet, although people have started making the bridal shower ritual, they seem to be reluctant to abandon the Javanese bridal showers. Â This study finds that the bridal shower trend is shaped and maintained continuously by party planners, parallel with the growth of the trend in other big cities in Indonesia. Interestingly, among the middle-class society, an image of becoming a part of a higher social class is produced when they throw a bridal shower and publish the event on social media.Â The findings of this research also indicate that the meaning and the values of bridal shower in Yogyakarta have shifted, which is believed to be the result of the misunderstanding of the very origin of the bridal showerÂ Bridal shower, sebuah ritual modern pada masyarakat Indonesia, juga dipraktikkan oleh masyarakat di Yogyakarta. Ritual ini mengadopsi praktik ritual â€˜American bridal showerâ€™ yang merupakan representasi dari kehidupan kelas atas dan ditunjukkan dengan menggunakan simbol kemewahan-tempat acara, dekorasi, akesoris, dan lainnya. Saat ini, praktiknya juga merambah kelas menengah. Acara ini menjadi bagian dari rangkaian acara menjelang pernikahan. Tulisan ini melihat bahwa tren bridal shower dibentuk dan dipelihara oleh penyedia jasa party planner. Seiring dengan berkembangnya ritual ini di kota besar lainnya- Jakarta, Bandung dan Surabaya. Bridal shower yang meriah merupakan simbol kemewahan. Bagi kelas menengah, citra untuk menjadi bagian dari kelas atas diproduksi melalui acara bridal shower dan mempublikasikannya melalui sosial media. Temuan penelitian ini menunjukkan adanya pergeseran makna dan nilai tentang bridal shower di Indonesia, yang dikarenakan adanya perbedaan pemahaman mengenai bridal shower di negara asalnya.Â Â Â Â